STRUCTURAL ANALYSIS OF EMOTIONS AND INTERNET ADDICTION BY MEDIATING LONELINESS IN ENGINEERING STUDENTS - maasoumeh Azizi (آموزش مهندسی ایران, 2021)
The present study was conducted with the aim of structural analysis of the relationship between emotions and internet addiction by mediating loneliness in students. The study method was correlation and statistical population was all students of Zabol University Faculty of Engineering in the academic year of 2019-2020 (about 1300 people). A total of 297 people selected by use the suitable sample size for structural research and stratified random sampling methods. They were completed the Young Internet Addiction (IAT), Single Emotion (SLFS) and Positive Negative Emotion (PANAS) questionnaire’s. The data were analyzed using SPSS and Lisrel software, as well as descriptive statistics and path analysis indicators. The results of Pearson correlation coefficient showed that there is a significant relationship between all research variables (p < 0.001). In addition, the overall indicators of the proposed correction model indicated good pattern fit (CFI= 1.00, AGFI= 0.97, GFI= 1.00, RSMEA= 0.03, χ2 / df= 1.38). According to the findings of the structural analysis of the research, it is necessary to teach engineering students the proper use of the internet, as well as how to cope with feelings of loneliness and enjoy positive emotions.